Determinants of Marketing Performance: Innovation, Market Capabilities and Marketing Performance - Farida, Naili (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2016)
This research aim to analyze causality influence between innovations, market capability, social modal, entrepreneurs oriented into marketing performance. Organizational innovations is a basic focus on Total Quality Management. Innovation has a role to technological development and competitive economy environment. The sample technique used is Purpusive sampling amount 58 respondent owner of Batik Small Medium Enterprise known as UKM. Small businesses have small medium or medium can grow and develop so that it is able to increase its product and sustainability efforts on the creative industry. The technique analysis used is Parsial Least Square (PLS), this result shows entrepreneur orientation doesn’t influence into market capability and social modal, innovation has positive influence and significance into market capability and marketing performance. This results shows innovation has important role in advantaging market capability while influencing to increase marketing performance of Small Medium Enterprise known as UKM. Penelitian ini bertujuan untuk menganalisis pengaruh kausalitas antara inovasi, kemampuan pasar, modal sosial, pengusaha berorientasi ke kinerja pemasaran. Inovasi organisasi adalah dasar TQM. Inovasi mempunyai peran pentinga dalam pengembangan teknologi dan lingkungan yang penuh persaingan. Teknik sampel yang digunakan adalah Purposive Sampling jumlah 58 pemilik responden dari Batik Kecil Menengah dikenal sebagai UKM. UKM dapat tumbuh dan berkembang melalui industri kreatif. Teknik analisis yang digunakan adalah Parsial Least Square (PLS), hasil ini menunjukkan orientasi entrepreneur tidak mempengaruhi ke kemampuan pasar dan modal sosial, inovasi berpengaruh positif dan signifikan dalam kemampuan pasar dan kinerja pemasaran. Hal ini menyebabkan menunjukkan inovasi memiliki peran penting dalam advantaging kemampuan pasar sementara yang mempengaruhi untuk meningkatkan kinerja pemasaran Kecil Menengah dikenal sebagai UKM.